Effects of the ECHO tele-mentoring program on HIV/TB service delivery in health facilities in Zambia: a mixed-methods, retrospective program evaluation - Brian Mubanga; Sombo Fwoloshi; Lastina Lwatula; Nomsa Siamwanza; Khozya Zyambo; Henry Sichinga; Hannah Tappis; Lloyd B. Mulenga; Aurthur Moonga; Lunga Ziko; Faith Simushi; Harry Madimba Massamba; et al. (BMC, 2023)
Abstract Background In the quest to ensure that quality healthcare is provided to all citizens through building healthcare worker capacity and extending reach for expert services, Zambia's Ministry of Health (MoH) in collaboration with its partners PEPFAR through the CDC and HRSA, began to implement the Extension for Community Healthcare Outcomes (ECHO) tele-mentoring program across the country through the Health Workers for the 21st Century (HW21) Project and University Teaching Hospital HIV/AIDS Project (UTH-HAP). This ECHO tele-mentoring approach was deemed pivotal in helping to improve the human immunodeficiency virus (HIV) service delivery capacity of health care workers. Method The study used a mixed method, retrospective program evaluation to examine ECHO participants' performance in the management of HIV/AIDS patients in all the 10 provinces of Zambia. Case presentation A phenomenological design was applied in order to elicit common experiences of ECHO users through focus group discussions using semi-structured facilitation guides in four provinces (Eastern, Lusaka, Southern and Western) implementing ECHO tele-mentoring approach. These provinces were purposively selected for this study. From which, only participants that had a monthly frequency of ECHO attendance of ten (10) and above were selected. The participants were purposively selected based on the type of cadre as well as facility type so that the final sample consisted of Doctors, Nurses, Midwives, Clinical Officers, Medical Licentiates, Pharmacy and Laboratory Personnel. All sessions were audio recorded and transcribed by the data collectors. A thematic content analysis approach was adopted for analyzing content of the interview's transcripts. Results Enhanced knowledge and skills of participants on HIV/TB improved by 46/70 (65.7%) in all provinces, while 47/70 (67.1%) of the participants reported that ECHO improved their clinical practice. Further, 12/70 (17.1%) of participants in all provinces reported that presenter/presentation characteristics facilitated ECHO implementation and participation. While, 15/70(21.4%) of the participants reported that ownership of the program had contributed to ECHO implementation and participation. Coordination, another enabler accounted for 14/70 (20%). Inclusiveness was reported as a barrier by 16/70 (22.8%) of the participants while 6/70 (8.6%) of them reported attitudes as a barrier (8.6%) to ECHO participation. In addition, 34/70 (48.6%) reported poor connectivity as a barrier to ECHO implementation and participation while 8/70 (11.5%) of the participants reported that the lack of ownership of the ECHO program was a barrier. 22/70 (31.4%) reported that increased workload was also a barrier to the program's implementation. Conclusion Consistent with its logical pathway model, healthcare providers' participation in ECHO sessions and onsite mentorship contributed to improved knowledge on HIV/TB among health care providers and patient health outcomes. In addition, barriers to ECHO implementation were intrinsic to the program its self, such as coordination, presenter and presentation characteristics other barriers were extrinsic to the program such as poor connectivity, poor infrastructure in health facilities and negative attitudes towards ECHO. Improving on intrinsic factors and mitigating extrinsic factors may help improve ECHO outcomes and scale-up plans.